2008
DOI: 10.1139/h08-050
|View full text |Cite
|
Sign up to set email alerts
|

The effect of inspiratory muscle training on high-intensity, intermittent running performance to exhaustion

Abstract: The effects of inspiratory muscle (IM) training on maximal 20 m shuttle run performance (Ex) during Yo-Yo intermittent recovery test and on the physiological and perceptual responses to the running test were examined. Thirty men were randomly allocated to 1 of 3 groups. The experimental group underwent a 6 week pressure threshold IM training program by performing 30 inspiratory efforts twice daily, 6 d/week, against a load equivalent to 50% maximal static inspiratory pressure. The placebo group performed the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 30 publications
3
58
1
2
Order By: Relevance
“…As expected, following the IMT, the global IM function of both groups improved significantly. For example, P 0 , increased by an average of 23%, which is similar to changes observed using identical IMT in previous randomised, placebocontrolled trials (21,25). Global CM function, as assessed by the SEPT, also improved in response to IMT, and the change was correlated with the improvement in P 0 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As expected, following the IMT, the global IM function of both groups improved significantly. For example, P 0 , increased by an average of 23%, which is similar to changes observed using identical IMT in previous randomised, placebocontrolled trials (21,25). Global CM function, as assessed by the SEPT, also improved in response to IMT, and the change was correlated with the improvement in P 0 .…”
Section: Discussionsupporting
confidence: 83%
“…In a previous study we have demonstrated that the response to a similar treadmill interval training is enhanced by a preceding period of IMT (26). Moreover, the improved breathing pattern, post-exercise P 0 , and RPB in the post-intervention ISO trial suggested that the enhanced IM function resulting from the IMT might have alleviated the IM fatigue and breathing effort during the running exercise, and, contributed to the enhancement of the exercise performance (25). Given that our combination of interval training, preceded by IMT, has already been shown to maximise the outcome of interval training, it is all the more impressive that the addition of CM/IM improved performance still further.…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, in two separate studies Tong et al (Tong and Fu. 2006;Tong et al 2008) report a two-fold greater reduction in dyspnoea during the Yo-Yo test after an IMW (-15 22%) compared to 6-weeks inspiratory muscle training (-11%), despite a much smaller increase in MIP after IMW (9 vs. 32%). Comparable improvements in Yo-Yo test running performance were also observed following an IMW (13-19%) and inspiratory muscle training (16%).…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve the efficiency of the gas exchange system and respiratory muscles, techniques such as specific inspiratory or expiratory muscle training or hyperpnoea training have been introduced [9][10][11][12]. Several authors reported that these methods improve breathing efficiency by increasing tidal volume while decreasing respiratory rhythm, resulting in a decrease in submaximal and an increase in maximal ventilation efficiency [9,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors reported that these methods improve breathing efficiency by increasing tidal volume while decreasing respiratory rhythm, resulting in a decrease in submaximal and an increase in maximal ventilation efficiency [9,13,14]. Furthermore, increased respiratory muscle strength following inspiratory training may contribute to a reduction in relative tension during submaximal exercise [14,15].…”
Section: Introductionmentioning
confidence: 99%